2021
DOI: 10.5334/aogh.3172
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Rwanda: Innovative Strategies for Prevention and Containment of COVID-19

Abstract: Introduction: Rwanda has made significant advancements in medical and economic development over the last 20 years and has emerged as a leader in healthcare in the East African region. The COVID-19 pandemic, which reached Rwanda in March 2020, presented new and unique challenges for infectious disease control. The objective of this paper is to characterize Rwanda’s domestic response to the first year of the COVID-19 pandemic and highlight effective strategies so that other countries, including high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 6 publications
0
27
0
3
Order By: Relevance
“…Even in the public health literature, calls have been made to moderate the containment measures in order to protect livelihoods, food security, and wellbeing ( Adams et al, 2021 ; Meyerowitz-Katz et al, 2021 ). For example, Rwanda and Vietnam have been rightly praised for exemplary containment of COVID-19 ( Karim et al, 2021 , Van Tan, 2021 ), but during the periods of stringent restrictions, we observed severe food insecurity outcomes. Media analysis from five African countries has shown that popular narratives often framed the situation as a balance between containment of the COVID-19 virus and food security; and that this was a hot topic in all five of the locations studied ( Birner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Even in the public health literature, calls have been made to moderate the containment measures in order to protect livelihoods, food security, and wellbeing ( Adams et al, 2021 ; Meyerowitz-Katz et al, 2021 ). For example, Rwanda and Vietnam have been rightly praised for exemplary containment of COVID-19 ( Karim et al, 2021 , Van Tan, 2021 ), but during the periods of stringent restrictions, we observed severe food insecurity outcomes. Media analysis from five African countries has shown that popular narratives often framed the situation as a balance between containment of the COVID-19 virus and food security; and that this was a hot topic in all five of the locations studied ( Birner et al, 2021 ).…”
Section: Discussionmentioning
confidence: 70%
“…Vietnam and Rwanda both implemented very well organised and stringent containment measures, including curfews, contact tracing, and strict social distancing regulations; operating a “go hard and go fast” approach which has been widely praised in both popular and academic literature (e.g. Karim et al, 2021 ; Van Tan, 2021 ; Cahan, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The pandemic, including the development of innovative management and treatment approaches [ 43 ] coupled with innovative approaches to teaching, has also provided an opportunity for African universities to showcase their skills to attract future investment. We have already seen apps being developed in South Africa to rapidly assess the use of antimicrobials among patients in hospitals given current concerns [ 17 , 110 , 139 , 140 ], with such approaches likely to grow, building on the greater use of technologies to manage patient care across Africa and the wider world [ 43 , 75 , 141 , 142 , 143 ].…”
Section: Discussionmentioning
confidence: 99%
“…Everyone tested COVID-19 positive, laboratory system automatically sends his or her details to contact tracing system that enables the tracers to start investigation immediately. 8 Investigation is performed by interviewing persons at the treatment centre or at home for those under home-based care programme. However, extra information about contacts are also generated through algorithms in place that are using combination of telephone numbers and network connectivity used by a positive case in the last 7 days prior to test positive.…”
Section: Data Sourcementioning
confidence: 99%